Liturgical pharmacology: Time of the question, complexity and ethics - Toit, Calvyn C. du (HTS teologiese studies, 2016)
Bernard Stiegler depicts technics as the human’s tertiary memory retention generating a pharmakon with both curative and malignant potential. He additionally rues the posthuman epoch’s depletion of a ‘time of the question’: revealed in the prevalent inaptitude for wisdom – scilicet long-term acuity. We offer Christian liturgy as an abeyant psychotechnique arcing the current pharmakon to cure through soliciting a ‘time of the question’. Rejuvenating Christian liturgy as a psychotechnique can bolster a broader societal ‘time of the question’. Firstly, we describe technic’s du jour mise on scène. Secondly, we constrain Christian liturgies as complex systems incorporating malleability, temporality, and instability. Thirdly, we imagine Christian liturgy as empty tradition allowing amateur repetition of ancient art enticing a ‘time of the question’.Keywords: Liturgy; Ethics; Technology; Stiegler; Complexity; Paul Cilliers; Van Huyssteen